Peran Orang Tua dalam Pencegahan Karies Gigi pada Anak Pra Sekolah (3-5 Tahun) di TK Aisyiyah 2 Pekanbaru - Wiwik Norlita; Isnaniar Isnaniar; Mochammad Hidayat (LPPM Universitas Muhammadiyah Riau, 2020)
Dental caries is a hard tissue disease caused by bacterial activity. Dental caries can occur in any child which can occur on a tooth surface and can extend to the deeper part of the tooth. The purpose of this study was to determine the role of parents in the prevention of dental caries in pre-school children at TK Aisyiyah 2 Pekanbaru. The type of research used is descriptive with total sampling techniques, totaling 64 respondents. Data collection tools using a questionnaire and data analysis used is univariate. The results of the study which was carried at TK Aisyiyah 2 Pekanbaru, the majority of parents' roles in preventing caries in pre-school age children were in the bad category of 62.5 %. There are 40 respondents who have a bad role in preventing the occurrence of dental caries in pre-school children. The results of this study are expected to the parents to be able to implement a clean and healthy lifestyle to prevent dental caries in pre-school children